Optimal Siting of Distributed Generation Unit in Power Distribution System considering Voltage Profile and Power Losses. (10th January 2022) - Aman, Muhammad Aamir; Ren, Xin Cheng; Tareen, Wajahat Ullah Khan; Khan, Muhammad Abbas; Anjum, Muhammad Rizwan; Hashmi, Anas M.; Ali, Haider; Bari, Inam; Khan, Jehanzeb; Ahmad, Sanaullah
Abstract : Many underdeveloped countries are facing acute shortage of electric power and short term measures are important to consider to address the problems of power outage, power plant failures, and disaster areas. Distributed generation (DG) is a promising approach for such cases as it allows quick on-site installation and generation of electric power. Injection of DG can improve the system voltage profile and also reduce the system's total power losses. However, the placement and sizing of the DG unit is an optimization problem in the radial distribution system. As a test case, this study examines voltage profile improvement and system power losses for an 11 KV residential feeder at the Abdul Rehman Baba grid station in Pakistan, which is modelled using the Electrical Transient Analyzer Program (ETAP). For various scenarios, several tests are conducted to assess the effects of DG on the distribution system. The results show that proper design considerations of size and location of a DG, to be inserted in to the system, lead to significant reduction in power losses and improvement in voltage profile and thus improvement in the overall efficiency of the power system. The projections of this work can be used to optimize the expansion of a power system and tackling different issues related to voltage profile in distribution sector worldwide.